Description of a new genus of Euliina with unique coupling adaptations of the male and female (Lepidoptera: Tortricidae: Tortricinae: Cochylini) - Santa-Rita, Jose V. Pérez; Baixeras, Joaquin (Zootaxa, 2017)
Ancoruncus langeri, new genus and new species, is described and illustrated from the Neotropics (Bolivia). It is assigned to the tribe Cochylini (subtribe Euliina) in the family Tortricidae. Ancoruncus langeri is characterized by an unusual, strongly developed uncus, distally expanded into an anchor-like, bilobed apical process and a complex gnathos in male genitalia, as well as an unusual configuration of the anterior lobes of the papillae anales, and tergum 8 with the anterior area bearing a double pocket in the female genitalia. The hypothetical dorsal coupling mechanism of the male and female genitalia is discussed.